Das Bildprogramm der Meleager-Platte aus dem Seuso-Schatz - Gesztelyi, Tamás (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
There are eight distinct love stories on the Meleager plate of the Seuso treasure. In four of them hunting plays an important role. The main theme of the depicted stories is allprevailing love, the emotion that is the motivating force in human life. An ancillary theme of the stories is hunting, which can be interpreted in a concrete as well as a figurative sense. Hunting is an aristocratic pleasure but at the same time it represents the exercise of virtues, too, in which even females can participate, cf. the scenes with Helene and Atalante. Although there is no need to look for a topical event to feature the motif of love, it is tempting to determine the contemporary function of the treasure as a wedding gift. We are inclined to believe that Seuso, the well-off owner of the treasure, must have been given this unique silver tableware as a wedding gift some time around the beginning of the 5th century.